Assessment Of Building Fragility Curve Due To Earthquake Excitation - Saruddin, Siti Nur Aqilah (2017)
In this study, the main objective is to develop fragility curve of regular and irregular moment-resisting frame based on different types of structural material, height, and ground motion records. 6 sets of concrete and steel frames were used in this study and varied in terms of heights which are 3-, 6- and 9-storey for regular and irregular frame. Each structure frames was designed based on Eurocode 2 and 3 with the aid Eurocode 8 for earthquake loading. The SAP2000 was used as the main tool to carry out the analysis. A pushover analysis (POA) was performed to get the performance of the structure due to static load. Triangular load was used to produce base shear-drift relationship. Then, an incremental dynamic analysis (IDA) was carried out with 3 ground motion records for each set near and far field. In addition, the Ranau earthquake also considered in this study for two types of case; single and repeated earthquake. While to develop the fragility curve, the result from IDA will be used as the main parameters. The IDA curves were compared with five level of performance level from Xue et al. (2008) study which are operation phase (OP), immediate occupancy (IO), damage control (DC), life safety (LS), and collapse prevention (CP). On the basis of the result of this thesis, it can be concluded that from POA result showed regular frames demonstrate a higher demand compared to irregular frames for concrete and steel frames. From the IDA results, it was proven that regular frames perform better for both materials under near and far field records. Based on the fragility curves developed for the near and far field records, irregular frames showed a higher probability of reaching or exceeding the performance level for concrete frame. On the other hand, regular steel frames showed a higher probability of reaching and exceeding the performance level.